Genetic polymorphism of CYP2C9 in patients on warfarin therapy and the clinical relevance / Teh Lay Kek... [et al.] - Teh, Lay Kek; Salleh, Mohd Zaki; Ismail, Rusli; Ahmad Ishak, Amiruddin (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2007)
Optimization of warfarin therapy has been difficult and pharmacogenomics has potential in offering clinically and economically useful interventions. We thus evaluated distribution of CYP2C9 which metabolises warfarin among patients prescribed warfarin to bridge the importance of CYP2C9 genotyping in warfarin management. A total of 189 patients on warfarin therapy in a local hospital were recruited after written informed consent. Their medical records were reviewed. Five milliliters of blood was taken from each subject and DNA was isolated and used for identification of CYP2C9 allele *2, *3 and *4 using nested-allele-specific-multipiex- PCR. Half of the patients were Malays and the remaining were Chinese. Two different genotypes were detected among the patients, 93.7% had CYP2C9*1/*1 and 6.3% were CYP2C9*1/*3. With standard clinical practice, the warfarin doses prescribed ranged from 1 to 8 mg (mean = 3.31 mg) while the mean of iNR achieved was 2.19 (S.D.0.86; range 0.86 to 5.69). The mean dose prescribed was higher in patients with genotype of CYP2C9*1/*1 (3.3S mg; SD 1.35 vs. 2.37 mg; SD 1.05; p = 0.007). Twelve subjects had INR level less than 1 and doses ranged from 1.5 to 6 mg {mean= 3.83). Ail of them had genotype CYP2C9*1/*1. Forty-eight-percent of the patients with wild-type variant have INR value of 2 to 4 given mean dose of 3.38 {SD 1.34) while 2/3 of the patients with heterozygous *3 achieved desirable INR for a mean dose of 2.37. Seven patients with wild-type variant had INR value of more than 4 (mean 4.95: range 4.15 to 5.69} givens dose of 1 to 5 mg of warfarin. The discrepancies observed are due to other factors including patients' compliances, drug interaction or patients having alleles not determined in this study. Even the mean for doses and INR between the 2 genotypes groups were similar, the standard error means were 3 times larger for patients with CYP2C9*1/*3 compared to wild-type. Current dosing protocol for warfarin lacked efficiency and screening for CYP2C9 may allow clinicians to develop protocols with increased therapeutic effectiveness.